Effective method to control the levitation force and levitation height in a superconducting maglev system - 杨芃焘 杨万民 王妙 李佳伟 郭玉霞 (Chinese physics B, 2015)
The influence of the width of the middle magnet in the permanent magnet guideways （PMGs） on the levitation force and the levitation height of single-domain yttrium barium copper oxide （YBCO） bulks has been investigated at 77 K under the zero field cooled （ZFC） state. It is found that the largest levitation force can be obtained in the system with the width of the middle magnet of the PMG equal to the size of the YBCO bulk when the gap between the YBCO bulk and PMG is small. Both larger levitation force and higher levitation height can be obtained in the system with the width of the middle magnet of the PMG larger than the size of the YBCO bulk. The stiffness of the levitation force between the PMG and the YBCO bulk is higher in the system with a smaller width of the middle magnet in the PMG. These results provide an effective way to control the levitation force and the levitation height for the superconducting maglev design and applications.